Tinjauan Perkembangan Keris Tangguh Ngentha-Entha Yogyakarta 1975-2015 - Supriaswoto Supriaswoto Supriaswoto; SP. Gustami SP. Gustami SP. Gustami; Timbul Haryono; R.M. Soedarsono R.M. Soedarsono R.M. Soedarsono (LP2M ISBI Bandung, 2015)
ABSTRACTEvery keris possesses its own chracteristic called tangguh. There is a keris with a characteristic called tangguhngéntha-éntha which was created within the Ngéntha-ÉnthaVillage community, lo- cated to the west of Godean District, in the Sleman Regency, Yogyakarta. The prominent figure behind the establishment of that forge (besalèn) was Empu (Ironsmith) Wayang, that one day moved from Mataram Kingdom at Kartasuro to that village. In 1963, Empu Supowinangun, the heir of Empu Wayang, passed away. As a result, since that time the process of making the keris with ngéntha-énthacharacteristic was no longer conducted. In 1975 there was an effort to revitalize it and succeded. This research was conducted to investigate this revitalization by using historical method. The result of this research demonstrates that this revitalization has been conducted succesfully by two master keris-makers (empu) named Yosopangarso and Jeno Harumbrojo, after received mental endorsement and financial support from two foreigners named Garrett Solyom and Dietrick Dreschler. The two master keris-makers already passed away and today the process of making the keris with tangguh ngéntha-éntha characteristic is taken over by Empu Sungkowo, Jeno Harumbrojo’s former adopted child. It is not clear who is supposed to be Sungkowo’s heir. It generates a lot of worry among people of the possibility that this style of keris will decline like what happened in 1963.Key words : keris with tangguhngéntha-énthacharacteristic, revitalization, Master Keris-makersYosopangarso, Jeno Harumbrojo, Sungkowo. ABSTRAKSetiap keris memiliki ciri tersendiri yang disebut tangguh, seperti tangguhngéntha- énthayang diciptakan di lingkungan masyarakat Desa Ngéntha-Éntha. Tokoh penting yang membuat keris dengan tangguh ini adalah Empu Wayang. Pada tahun 1963, Empu Supowinangun, pewaris Empu Wayang, meninggal dunia. Akibatnya, sejak saat itu pembuatan keris dengan gaya ngéntha-éntha tidak lagi dilakukan. Pada tahun 1975 ada upaya untuk merevitalisasinya dan berhasil. Penelitian ini bermaksud meneliti revitalisasi keberadaan keris Tangguh Ngenta-entha tersebut dengan menggunakan metode historis. Hasil penelitian ini menunjukkan bahwa revitalisasi ini telah diakukan oleh dua empu keris bernama Yosopangarso dan Jeno Harumbrojo. Dewasa ini, dua orang empu keris t e r s e b ut t e l a h m e n i n g g a l d un i a d a n pr o s e s pe m b ua t a n k e r i s d e n g a n c i r i - c i r i tangguhngéntha-énthadiambil alih oleh Empu Sungkowo, anak angkat Empu JenoHarumbrojo dengan metode rekonstruksi pola-pola pewarisan yang tetap dan tidak meninggalkan pakem-pakem tradisi yang ada.Kata kunci: revitalisasi, keris, gaya ngéntha-éntha